FIRE RETARDANT PROPERTIES OF POLYESTERSULFONE KETONES - Rayimov Zukhriddin Khayriddin ogli; Haydarov Axtam Amonovich; Haytiyev Shaxruz Botir ogli (American Journals, 2024)
Currently, a large number of methods for the synthesis of block copolymers make it possible to combine an unlimited number of different molecules and synthesize a large number of block copolymers. The thermal and mechanical properties and stability of the synthesized block copolymers vary widely. Newly synthesized block copolymers and copolymers can be used as heat-resistant structural and film materials in various fields of modern industry (automotive, electronics, electrical, aviation, chemical industries).
Keywords: Oxygen index (OI), destruction products, aromatic polymers, the pre-fire zone, polyestersulfone ketone, polyarylates, fire-resistant polymers